2014
DOI: 10.1186/1750-1172-9-45
|View full text |Cite
|
Sign up to set email alerts
|

Patients with type 1 Gaucher disease in South Florida, USA: demographics, genotypes, disease severity and treatment outcomes

Abstract: BackgroundGaucher disease, an autosomal recessive condition due to deficiency of lysosomal glucocerebrosidase, is a multisystemic disease, with variable age of onset, severity and progression. It is classified into subtypes delineated by the absence (type 1) or presence (type 2 and 3) of primary nervous system involvement.The ethnically diverse, largely immigrant population in South Florida has a spectrum of Gaucher disease phenotypes, creating a challenge for optimization of disease management and an opportun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…The most common ethnic origins in Ontario are Canadians, followed by English, Scottish, and Irish 40 . Accordingly, this patient cohort has similar genotype composition when compared to the United Kingdom/ Ireland population: N370S/N370S (29.4% vs. 30.3%) and N370S/other 36.5% vs. 40.0%), except for N370S/L444P (21.2% vs. 3.3%) 30 . Similarities were also observed when compared to the World ICGG Registry, in N370S/N370S (29.4% vs. 24.0%) and N370S/L444P (21.2% vs. 18.1%), except for N370S/other ( 36.5% vs. 46.7%) 30 .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The most common ethnic origins in Ontario are Canadians, followed by English, Scottish, and Irish 40 . Accordingly, this patient cohort has similar genotype composition when compared to the United Kingdom/ Ireland population: N370S/N370S (29.4% vs. 30.3%) and N370S/other 36.5% vs. 40.0%), except for N370S/L444P (21.2% vs. 3.3%) 30 . Similarities were also observed when compared to the World ICGG Registry, in N370S/N370S (29.4% vs. 24.0%) and N370S/L444P (21.2% vs. 18.1%), except for N370S/other ( 36.5% vs. 46.7%) 30 .…”
Section: Discussionmentioning
confidence: 81%
“…There have been several studies examining the epidemiological profiles of GD in specific regions such as France 21 , Brazil 29 , Iberia 9 , and South Florida 30 , but none in Canada. Ontario is the highest populated province in Canada, consisting of 38.5% of the population 31 , the largest share (53.3%) of immigrants 32 , and more than half (57.9%) of Ashkenazi Jews 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the diagnosis of GD in many of these cases was based solely on the visualization of Gaucher cells, which can be difficult to distinguish from pseudo-Gaucher cells present in other diseases. 3 Wasserman et al (writing in 1955) were the first to report of Coombs-positive hemolytic anemia in GD, 22 which was followed by several case series consistent with a 0.55%-2.7% rate of AIHA in GD patients 10,27,[29][30][31] and several additional cases (Table 1). 4,32 Autoimmune hemolytic anemia (AIHA) is reported to be more common in GD patients than in the general population, which has an annual incidence of 1 in 100,000 (0.001%).…”
Section: Discussionmentioning
confidence: 98%
“…In the largest (n = 8069), 0.11% of the population were homozygous for any mutation, the majority of which were N370S/N370S genotypes (0.10%); 6.5% were identified as a carrier of a GD genotype, most of which had an N370S mutation (6%) [41]. In a fifth study that retrieved the records of 93 South Florida patients with GD1 from the International Collaborative Gaucher Group (ICGG) Gaucher Registry, 61.9% were shown to be homozygous for the N370S mutation [43]. These findings are most likely a consequence of the large AJ population of South Florida.…”
Section: Prevalencementioning
confidence: 99%
“…In one study, age at GD1 diagnosis was reported by genotype: mean age at diagnosis was older than 10 years for patients with genotypes N370S/?, N370S/N370S, N370S/L444P, and N370S/rare allele; age at diagnosis of younger than 10 years was reported in patients with N370S/ 84GG, L444P/L444P, L444P/?, and N370S/IVS2+1 genotypes all of which are often associated with severe GD symptomatology [3]. Three additional studies reported a mean age at diagnosis ranging from 6 years in the Moroccan study of 11 patients to 50 years in 93 patients from South Florida included in the ICGG Gaucher Registry [43,44]; the Moroccan study also identified two cases of GD2 diagnosed at 3 months and 18 months, respectively; age at diagnosis of seven GD3 cases ranged from 10 months to 2 years and 7 months in a study of Taiwanese patients [58]. In a multinational observational study (24-month study duration) enrolling all non-Ashkenazi patients (who had been seen for a hematological evaluation), the mean age at diagnosis was 32.6 years [60].…”
Section: Age and Timeliness Of Diagnosis Of Gdmentioning
confidence: 99%